Moisture processes in the operational quasi-geostrophic model - RAMANATHN , Y.; BANSL, R. K. (MAUSAM, 1976)
Five-layer quasi-geostropbic model with input data at 850, 700, 500, 300 and 100mb is being run on an operational basis once a day.24 hour’s forecast of contour heights at the above levels and vertical velocity (w) values at 200, 400, 600 and 800mb are obtained. The model includes orography, cumulus scale heating in the tropical domain of the forecast area. The area of integration is from 40° to 120° E and 5.0° to 42.5°N at 2.5° grid interval. The model boundary values are generated from a bigger coarse mesh area from 0° to 140° and 00 to 60oN at 5° interval.